2014
DOI: 10.7197/cmj.v36i4.5000006305
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiyaliz hastalarında uyku kalite bozukluğu ve huzursuz bacak sendromu arasındaki ilişki

Abstract: Amaç. Huzursuz bacak sendromu (HBS) bacaklarda huzursuzluk hissi, yanma ile kendini gösteren istirahat ve geceleri daha sık olan bacakları hareket ettirme isteği ile karakterize bir rahatsızlıktır. Bu durum hemodiyaliz hastalarında sıktır ve uykusuzluğa neden olabilir. Biz çalışmamızda uyku kalitesinde bozukluk ile HBS arasındaki ilişkiyi incelemeyi amaçladık. Yöntem. Çalışmaya hemodiyaliz programında olan hastalar alındı. Hastalara Uluslar arası huzursuz bacak çalışma grubu tanı kriterleri kullanıldı ve uyku … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Huzmeli et al found no significant relation between SQ and serum parathormone, calcium and phosphorus levels in the study with 112 hemodialysis patients (22). Similarly, Sabbatini et al couldn't find any relation between SQ and PTH levels in 78 CKD patients in various stages (23).…”
Section: Table IV -Multivariate Logistic Regression Analysis For Poor...mentioning
confidence: 88%
“…Huzmeli et al found no significant relation between SQ and serum parathormone, calcium and phosphorus levels in the study with 112 hemodialysis patients (22). Similarly, Sabbatini et al couldn't find any relation between SQ and PTH levels in 78 CKD patients in various stages (23).…”
Section: Table IV -Multivariate Logistic Regression Analysis For Poor...mentioning
confidence: 88%
“…Studies have shown that individuals’ self-care agencies are affected by their bio-psycho-social status 6 , 7 , 8 . As with all risky diseases, sleep disorders are frequently encountered in patients with CKD and undergoing hemodialysis 9 , 10 . As a result, the mental health of individuals is adversely affected.…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing HD experience many ailments, including pain, fatigue, muscle cramps, nausea, vomiting, constipation, restless legs syndrome (RLS), and sleep disorders (Göriş et al, 2016; Song et al, 2021). Studies have indicated that the prevalence of RLS in patients receiving HD is 18.6%–66.1% and that it increases the severity of fatigue, and negatively impacts patients’ quality of life (QoL) (Giannaki et al, 2017; Hüzmeli et al, 2014; Kutlu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%